Giant sialolite in the submandibular gland: case report (Research, Society and Development, 2021)
Sialolith is a common pathology of the salivary glands, especially the largest, with the most affected submandibular gland in 80 to 90% of cases. This condition causes obstruction of the gland duct, generating accumulation of saliva, inflammation, infection, causing pain and discomfort to the patient. Smaller calculations do not exceed 10 mm, but larger than 15 mm are considered giants. The etiopathogenesis may be linked to the deposition of calcium in a matrix of cellular desquamation, foreign body, mucus, inside a duct. This article aims to report the diagnosis and treatment of an unusual case regarding the symptoms and size of a sialolith in the left submandibular gland.